Raja Yoga Sebagai Jalan Mencapai Pemahaman Akan Hakikat Brahman (Studi Kasus Pustaka Suci Bhagavad GÄ«tÄ) - Adnyana, Ida Bagus Putu (JURNAL YOGA DAN KESEHATAN, 2021)
Catur Yoga are four ways that humans can take to unite themselves with Brahman. The four paths include Karma Yoga, Bhakti Yoga, Raja Yoga, and Jnana Yoga. Of the four paths, this study will discuss Raja Yoga, which is the most difficult way or way for humans to do if it is done without the assistance of a spiritual teacher. Raja Yoga teachings emphasize the process of the self to be able to control all activities of the movement of the mind for the realization of a clear and good mind and always focus on Brahman. The state of the self that is able to control the movement of one's mind in the Yoga Sutras of Patanjali is called Citta Vrtti Nirodha. Citta Vrtti Nirodha will lead human life to Moksartham Jagadhita Ya Ca Iti Dharma. The teachings of Raja Yoga will be studied in depth and comprehensively using the literature study of the sacred literature of Bhagavad GÄ«tÄ as the main source.